Instantes cotidianos: por uma arte da fotografia móvel - Swarowsky, Luciana Abitante (2013)
The objective of this research, in visual poetic, is to investigate in a practicaltheoretical way, the photography production from the usage of a new media: the mobile phone. This research aims to question the mobile photography while photographic object, as question the ephemerid of photographic act through a mobile device. In the subjugate of the pre-established technical limitation, which is a mobile device characteristic, I am developing a poetic which works the photographic capture and post-capture in transit, the mobility. This is a poetic motivated by a growing potential that is reaching the mobile communication and that tries to include new media in daily basis. Therefore, we are being guided by electronic impulses and dialogs mediated by the machine. Through three-distinct operational process, from innumerous possible, I work the mobile photography searching ways to transform it in an expressive way of art. In the position of a armed subject and completely apparatus , with a camera always in hand, I tried to express an experience derived not only from my subjectivity while author and real subject, but also as a experience that elucidates the device chosen automatisms and, therefore, and automatized subject revealed, non-personalized. In this way, all the photographic production process, capture and post-capture, get instituted by an interactive dialog between subjectivity and automaticity.